A kind of magic the political marketing of the ANC - Ranchod, Rushil (Jacana Media, 2013)
"The story begins in 1955 with the adoption of the Freedom Charter, which became the platform on which the ANc subsequently constructed its image and its appeal. It was in exile, after its banning in 1960, that the ANC took political marketing seriously. There is fascinating evidence of how the ANC's Department of Information and Publicity tailored its messages to audiences inside the country and internationally ; and how it launched Mandela as a global icon, recognising that 'it is human interest that sells politics'. Subsequent chapters examine the 1994 and 2009 elections, publicity and marketing efforts around economic policy, and how effectively the ANC has marketed itself, its history, its role in the struggle, and its links with 'the people'. A Kind of Magic challenges us to rethink what we know about the ANC, its past, present and future place in South African political life." -- Back cover